Nghiên cứu phản ứng ankyl hóa benzen trên xúc tác MCM-22 biến tính - Thuận, Ngô Thị; Dũng, Công Tiến (Vietnam Journal of Chemistry, 2014)
The alkylation of benzene over Ga-MCM-22 zeolite by ethanol was performed successfully. The influence of temperature, space velocity, feed ratio and time-on-stream on the ethylation of benzene was investigated. It has been shown that Ga-MCM-22 was suitable for the ethylation of benzene with ethanol. Based on the experimental results, the dynamic and chemical mechanisms of the process were proposed.